2022
DOI: 10.3389/fpls.2022.925986
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Yield Estimation Based on Vegetation Indices and Texture Features Derived From RGB Image

Abstract: Yield monitoring is an important parameter to evaluate cotton productivity during cotton harvest. Nondestructive and accurate yield monitoring is of great significance to cotton production. Unmanned aerial vehicle (UAV) remote sensing has fast and repetitive acquisition ability. The visible vegetation indices has the advantages of low cost, small amount of calculation and high resolution. The combination of the UAV and visible vegetation indices has been more and more applied to crop yield monitoring. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The R 2 of the linear regression model ranged from 0.52 -0.65 and the R 2 of the machine learning model ranged from 0.57 -0.82. This is similar to the findings of Ma et al (2022) who used machine learning techniques and linear regression models to monitor cotton yield by integrating vegetation indices from RGB images. Zhang et al (2021) also found that the machine learning RF method has a more robust capability than MLR in terms of handling different remote sensing indices when estimating crop growth parameters using UAV, which further reduced the RRMSE by 2.74 -5.11% in the estimation of LAI and LDW.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The R 2 of the linear regression model ranged from 0.52 -0.65 and the R 2 of the machine learning model ranged from 0.57 -0.82. This is similar to the findings of Ma et al (2022) who used machine learning techniques and linear regression models to monitor cotton yield by integrating vegetation indices from RGB images. Zhang et al (2021) also found that the machine learning RF method has a more robust capability than MLR in terms of handling different remote sensing indices when estimating crop growth parameters using UAV, which further reduced the RRMSE by 2.74 -5.11% in the estimation of LAI and LDW.…”
Section: Discussionsupporting
confidence: 85%
“…Satellites are often limited by revisit periods and weather conditions, making it difficult to provide sufficiently effective data at critical stages of crop growth. Multiple sensors, such as multispectral and hyperspectral sensors, can capture a wealth of information, but storing and processing this data is not straightforward and can easily lead to data redundancy and wastage (Kong et al, 2019;Ma et al, 2022;Zhang et al, 2019). The collection of RGB images by UAV is simple, economical and easy to process (Yamaguchi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning algorithms combined with remote sensing data have been widely used in areas such as crop growth monitoring (Li et al, 2019;Zheng et al, 2019;Zhang et al, 2021), yield estimation (Fu et al, 2020;Garcıá-Martıńez et al, 2020;Ma et al, 2022) and disease identification (Guo et al, 2021;Zhu et al, 2022). This study used four machine learning algorithms, SVM, RF, BPNN and PLSR, to construct LAI monitoring models for different maize varieties.…”
Section: Comparison Of Different Machine Learning Modelsmentioning
confidence: 99%
“…The results of this study are similar to those of previous studies. Ma et al (2022) used color indices and texture features from UAV RGB images to accurately estimate cotton yield, with the RF_ELM model based on color indices and texture features having the highest accuracy (R 2 = 0.911). Yang et al (2021) used vegetation indices and texture features to achieve an estimation of LAI for rice at full fertility.…”
Section: Influence Of Uav Image Features Fusion On Lai Estimation Pot...mentioning
confidence: 99%